China meets digital currency: E-CNY and its implications for businesses - WANG, Heng (Institutional Knowledge at Singapore Management University, 2021)
China is likely to be the first major economy to issue central bank digital currency (CBDC). China’s CBDC, e-CNY, may lead to a new ecosystem that would profoundly affect business, product offerings and business practice. E-CNY is likely to affect both local and international businesses, particularly those with a presence in China or those who commonly transact with Chinese actors. There is also the possibility of e-CNY use outside of China. If China’s CBDC practice and standards affect international practice (such as through standard making), e-CNY has the potential to affect the broader businesses community. This article discusses the following crucial questions: how to understand e-CNY? What does e-CNY mean for local and international businesses? Businesses need to adequately prepare for a new business landscape with e-CNY that is not only a currency but also generates large amounts of data.